A 'Third World Feminist' Reading of Selected Malaysian Novels in English - Teh, Chee Seng (2003)
Feminist studies in the field of literary studies are still at its infancy in Malaysia, as represented by the marginalization of women and their issues from literary criticism. This study aims to charter new terrains in literary studies by looking at the representations of women as they are presented in six selected Malaysian novels in English. Women characters as they are portrayed in the novels are studied within the Third World Feminist theoretical framework. Third World feminist theory contest perceptions of women as they are observed by Western feminism which tends to universalize the experiences of women without considering the conjugation of feminism and various other factors such as race, culture and class. The purpose of this study is primarily to advocate the observation of women in literary discussion. The study reveals that women are represented in some of the novels as suppressed and dominated by men through marriage, attire, motherhood and other domains. A resultant from marriage is motherhood which inevitably leads to domestic responsibilities such as providing food. In addition, women are represented as victims of male aggression in which they become the recipients of violent acts such as rape and verbal abuse. Viewing women solely as victims of patriarchal aggression will result in the projection of monolithic images of women-as-victims. This study also indicates that women can concurrently be strong, powerful and decisive. They are not always the passive victims for they can be initiators, decision-makers or controllers of men and their circumstances. Finally, this study recommends that further studies are justified so as to add more knowledge to feminist studies which will be a means of empowering women and contesting patriarchal suppression.